Investigation of antioxidant vitamins (A, E and C) and selenium levels in chickens receiving estrogen or testosterone - Halifeoglu, I; Karatas, F; Canatan, H; Colak, R; Karadas, E (John Wiley & Sons Ltd, 2003)
In the present study estrogen or testosterone was administered to broiler chickens (6 weeks old) for 5 weeks and levels of antioxidant vitamins (A. E and C) and selenium (Se) were determined. In animals who received estrogen, vitamins A, E, C and Se levels were 0.70 +/- 0.19, 11.0 +/- 2.45, 20.0 +/- 5.17 and 130.0 +/- 25.0 mug l(-1), respectively. Vitamins A, E, C and Se levels in the testosterone-administered group were found to be 0.54 +/- 0.16, 9.9 +/- 1.96, 18.0 +/- 5.18 and 100.0 +/- 18.0 mug l(-1), respectively. Vitamins A, E, C and Se levels were found to be significantly increased in the estrogen-administered group compared to the controls (p < 0.01, p < 0.01, p < 0.05, p < 0.05, respectively). Although all parameters were increased in testosterone-treated animals, only increases in vitamins A and E were found to be statistically significant (p < 0.01, p < 0.01, respectively). Based on the present findings, estrogen and testosterone show direct antioxidant effects by increasing the activities of sonic enzymes and they also cause an increase in antioxidant vitamin levels and hence indirectly also contribute to antioxidant capacity. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: estrogen; testosterone; vitamin A; vitamin E; vitamin C; Se; HPLC